2015
DOI: 10.1021/jacs.5b11220
|View full text |Cite|
|
Sign up to set email alerts
|

Asymmetric Copper-Catalyzed Carbozincation of Cyclopropenes en Route to the Formation of Diastereo- and Enantiomerically Enriched Polysubstituted Cyclopropanes

Abstract: The enantioselective synthesis of cyclopropylzinc reagents has been achieved via a copper-catalyzed carbozincation of 3,3-disubstituted cyclopropenes with diorganozinc reagents. The obtained organozinc compounds can be easily functionalized with a broad range of electrophiles, including palladium-catalyzed cross-couplings, affording highly substituted cyclopropanes. The operationally simple procedure using very low quantities of a commercially available and inexpensive copper catalyst provides a new tool for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 60 publications
0
48
0
Order By: Relevance
“…As reported, [14] the catalytic diastereo-and enantioselective carbometalation of cyclopropenes 1 was easily achieved by addition of 1.5 equiv of Grignard reagent R 1 MgBr in the presence of acatalytic amount of copper salt Cu(CH 3 CN) 4 PF 6 (2 mol %) and chiral catalyst (R,S)-Josiphos (2.2 mol %) in Et 2 OatÀ5 8 8Cin30min (Scheme 2). As reported, [14] the catalytic diastereo-and enantioselective carbometalation of cyclopropenes 1 was easily achieved by addition of 1.5 equiv of Grignard reagent R 1 MgBr in the presence of acatalytic amount of copper salt Cu(CH 3 CN) 4 PF 6 (2 mol %) and chiral catalyst (R,S)-Josiphos (2.2 mol %) in Et 2 OatÀ5 8 8Cin30min (Scheme 2).…”
mentioning
confidence: 77%
“…As reported, [14] the catalytic diastereo-and enantioselective carbometalation of cyclopropenes 1 was easily achieved by addition of 1.5 equiv of Grignard reagent R 1 MgBr in the presence of acatalytic amount of copper salt Cu(CH 3 CN) 4 PF 6 (2 mol %) and chiral catalyst (R,S)-Josiphos (2.2 mol %) in Et 2 OatÀ5 8 8Cin30min (Scheme 2). As reported, [14] the catalytic diastereo-and enantioselective carbometalation of cyclopropenes 1 was easily achieved by addition of 1.5 equiv of Grignard reagent R 1 MgBr in the presence of acatalytic amount of copper salt Cu(CH 3 CN) 4 PF 6 (2 mol %) and chiral catalyst (R,S)-Josiphos (2.2 mol %) in Et 2 OatÀ5 8 8Cin30min (Scheme 2).…”
mentioning
confidence: 77%
“…The nature of the solvent (polar (fluorobenzene,c hlorobenzene, and THF) vs.non-polar (benzene and toluene)) did not have as ignificant influence on this reaction (entries 6a nd [8][9][10][11]. )i n8 5% yield in 48 h, but the enantioselectivity was rather poor (45 % ee,entry 2).…”
Section: Angewandte Chemiementioning
confidence: 95%
“…Extensive studies on the asymmetric hydroamination of alkenes have already been reported, but mostly focused on intramolecular reactions. [4] Regarding the asymmetric functionalization of cyclopropenes,v arious types of nucleophilic addition reactions,s uch as hydroboration, [5] hydrostannation, [6] hydroacylation, [7] hydroformylation, [8] and carbozincation, [9] have recently been reported. [4] Regarding the asymmetric functionalization of cyclopropenes,v arious types of nucleophilic addition reactions,s uch as hydroboration, [5] hydrostannation, [6] hydroacylation, [7] hydroformylation, [8] and carbozincation, [9] have recently been reported.…”
mentioning
confidence: 99%
“…79 Following the pioneering work by Nakamura and Lautens they were able to identify two chiral copper catalysts which efficiently furnished highly enantioenriched polysubstituted cyclopropanes. 80,81 Several features of the method are noteworthy: (1) the combination of highly encumbered phosphine ligand ( R )-DTBM-SEGPhos with Cu(CH 3 CN) 4 PF 6 or CuTC (copper( i ) thiophene-2-carboxylate) completely suppressed dimeric side products which appeared otherwise in significant amounts (typically 15–20%).…”
Section: Carbocupration Reactions Of Cyclopropenesmentioning
confidence: 99%